PENGARUH LAJU ALIRAN UDARA TERHADAP KARAKTERISTIKPEMBAKARAN BIOBRIKET DARI LIMBAH PENGGILINGAN PADI (SEKAM) - Laifa Rahmawati, Rizky Stiyabudi, dan Christin Lita Agustiani (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This reseach is aimed to study about the effect of air current velocity to the combustioncharacteristics of biobricket from chaff.This research is an experimental research with air current velocity as a independent variable.Air current velocity includes varies of air current velocity, 0,6 m/s, 0,8 m/s, and 1 m/s. The effect ofthese variables to the combustion characteristics of biobricket from chaff is analyzed from theresult of combustion test.From this research, it can be concluded that air current velocity is in a non‐straightcomparison with combustion temperature, combustion temperature is in a straight comparisonwith mass decreasing, combustion temperature is in a straight comparison with combustionvelocity, and air current velocity is in a non‐straight comparison with the mass decreasing andcombustion velocity.Key words: air current velocity, carbonation duration, biobricket, chaff